The maze runner - Dashner, James, 1972- (New York : Delacorte Press, 2009)
Sixteen-year-old Thomas wakes up with no memory in the middle of a maze and realizes he must work with the community in which he finds himself if he is to escape.
School Library Journal, October 2009
Publisher's Weekly, September 2009
Horn Book, April 2010
Bulletin (Center for Children's books), November 2009
Voice of Youth Advocates (V.O.Y.A.), December 2009
Kirkus Review, September 2009
Keywords: Amnesia -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Labyrinths -- Juvenile fiction; Amnesia -- Fiction; Cooperativeness -- Fiction; Labyrinths -- Fiction; Science fiction; Amnesia -- Fiction; Cooperativeness -- Fiction; Labyrinths -- Fiction; Science fiction; Science fiction